Penerapan Model Stad Berbantuan Media Ular Tangga terhadap Motivasi Belajar Siswa pada Materi Keliling dan Luas Bangun Datar Kelas V - Kristi, Tabita; Humairo, Yumna; Pratiwi, Eva; Firgiawan, Diva; Nawang, Dewi (Papanda Publisher, 2024)
This research aims to increase the mathematics learning motivation of class V students at SDN Mangkang Wetan 03, especially in understanding geometric concepts related to calculating the perimeter and area of ​​flat shapes. Initial observations show how difficult it is for students to understand the material and the lack of variation in the use of media and learning models. To overcome this problem, researchers applied the STAD type Cooperative Learning learning model with the help of the media